ANALISIS DETERMINAN PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DALAM KONTEKS MULTIKULTURAL - Masni, Masni; Tang, Muhammad (Fitrah, 2024)
The purpose of this article is to analysis the factors that influence the development of a multicultural PAI curriculum. The research method used by the author is the library method or literature review which involves critical analysis of journals, books and other sources. Then, the data analysis technique used is the interactive model as proposed by Miles & Huberman which includes three techniques, including reducing data, presenting data and drawing conclusions. Based on the data that has been analyzed, the research results illustrate that the development of a multicultural PAI curriculum is influenced by various complex factors. These factors consist of factors from within (internal) and factors from outside (external). Internal factors include: the vision and mission of the educational institution, values ​​and principles, as well as the competence of educators. Meanwhile, external factors include: education policies, community needs and demands, global developments, and social and political context. The implication of this writing is to provide insight and understanding for policy makers, education managers and educational practitioners to pay attention to these factors in developing a multicultural Islamic religious education curriculum.